2017
DOI: 10.1016/j.jacc.2017.04.042
|View full text |Cite
|
Sign up to set email alerts
|

Time-to-Furosemide Treatment and Mortality in Patients Hospitalized With Acute Heart Failure

Abstract: In this prospective multicenter, observational cohort study of patients presenting at the ED for AHF, early treatment with intravenous loop diuretics was associated with lower in-hospital mortality. (Registry focused on very early presentation and treatment in emergency department of acute heart failure syndrome; UMIN000014105).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
228
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 266 publications
(250 citation statements)
references
References 21 publications
14
228
0
8
Order By: Relevance
“…Briefly, 100% of cases admitted at each participating institution that fulfilled inclusion criteria were registered. Inclusion and exclusion criteria of each registry has been described elsewhere9, 10, 11; all 3 registries did not include patients complicated with acute coronary syndrome. Data collection was patient based, but not event based, among all registries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, 100% of cases admitted at each participating institution that fulfilled inclusion criteria were registered. Inclusion and exclusion criteria of each registry has been described elsewhere9, 10, 11; all 3 registries did not include patients complicated with acute coronary syndrome. Data collection was patient based, but not event based, among all registries.…”
Section: Methodsmentioning
confidence: 99%
“…The registry focused on REALITY‐AHF (very early presentation and Treatment in the emergency department of Acute Heart Failure syndrome) and was a prospective multicenter study (20 hospitals in all regions of Japan) that was designed to evaluate the association between time to treatment and clinical outcome in patients with AHF presenting at the ED 11. From August 2014 to December 2015, consecutive patients with AHF hospitalized through the ED at participating hospitals were included in the registry at the initial hospital admission and followed up.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, loop diuretics are given in multiple doses (twice to three times daily). Intravenous loop diuretics should be administered as early as possible, since early loop diuretic administration is associated with lower in‐hospital mortality . In the DOSE‐AHF trial, no difference was seen in the primary endpoint between continuous or bolus infusion.…”
Section: Practical Use Of Diuretics In Acute Heart Failurementioning
confidence: 99%
“…72 Similarly, early administration of serelaxin did not improve the composite endpoint of worsening HF at 5 days or CV death at 6 months in RELAX-AHF2. 73 Interestingly, an observational study suggested that treatment with intravenous loop diuretic within 1-h of presentation to the emergency department was associated with lower in-hospital mortality, 74 but the observational nature of this study precludes any conclusions regarding optimal type or timing of AHF interventions.…”
Section: Acute Heart Failurementioning
confidence: 88%